The Analysis of Sekartaji’s character Movement In Sekartaji Tandhing Dance - Trinil Windrowati (Sekolah Tinggi Kesenian Wilwatikta Surabaya, 2022)
The analysis of Sekartaji Tandhing’s movement in Sekartaji Tandhing dance aims at figuring out the factual factors and aspects of the characters in the movement found in Sekartaji Tandhing dance. By employing Agus Tasman’s Analysis of Dance Moves and Character, including space, time, energy, movement, and a character concept consisting of typology, character, and temperament, it was found that the Sekartaji Tandhing’s characters met a good quality of character and movement analysis. The inner and outer reflection used as aspects in analyzing the Sekartaji Tandhing’s characters discovered an aesthetic point that its beauty can be felt and was scientifically justified